Gene regulatory network underlying the immortalization of epithelial cells - Méndez López, Luis Fernando; Dávila Velderrain, José; Domínguez Hüttinger, Elisa; Enríquez Olguín, Christian; Martínez García, Juan Carlos; Alvarez Buylla Roces, María Elena (2017)
Abstract Background: Tumorigenic transformationofhumanepithelialcellsinvitrohasbeendescribedexperimentallyas thepotentialresultofspontaneousimmortalization.Thisprocessischaracterizedbyaseriesofcell–statetransitions,in whichnormalepithelialcellsacquirefirstasenescentstatewhichislatersurpassedtoattainamesenchymalstem–like phenotypewithapotentiallytumorigenicbehavior.Inthispaperweaimtoprovideasystem–levelmechanistic explanationtotheemergenceofthesecelltypes,andtothetime–orderedtransitionpatternsthatarecommonto neoplasiasofepithelialorigin.Tothisend,wefirstintegratepublishedfunctionalandwell–curatedmoleculardataof thecomponentsandinteractionsthathavebeenfoundtobeinvolvedinsuchcellstatesandtransitionsintoa networkof41molecularcomponents.Wethenreducethisinitialnetworkbyremovingsimplemediators(i.e.,linear pathways),andformalizetheresultingregulatorycoreintologicalrulesthatgovernthedynamicsofeachofthe networkcomponentsasafunctionofthestatesofitsregulators. Results: ComputationaldynamicanalysisshowsthatourproposedGeneRegulatoryNetworkmodelrecoversexactly threeattractors,eachofthemdefinedbyaspecificgeneexpressionprofilethatcorrespondstotheepithelial, senescent,andmesenchymalstem–likecellularphenotypes,respectively.Weshowthatalthoughamesenchymal stem–likestatecanbeattainedevenunderunperturbedphysiologicalconditions,thelikelihoodofconvergingtothis stateisincreasedwhenpro–inflammatoryconditionsaresimulated,providingasystems–levelmechanistic explanationforthecarcinogenicroleofchronicinflammatoryconditionsobservedintheclinic.Wealsofoundthat theregulatorycoreyieldsanepigeneticlandscapethatrestrictstemporalpatternsofprogressionbetweenthesteady states,suchthatrecoveredpatternsresemblethetime–orderedtransitionsobservedduringthespontaneous immortalizationofepithelialcells,bothinvivoandinvitro. Conclusion: Ourstudystronglysuggeststhattheinvitrotumorigenictransformationofepithelialcells,which stronglycorrelateswiththepatternsobservedduringthepathologicalprogressionofepithelialcarcinogenesisinvivo, emergesfromunderlyingregulatorynetworksinvolvedinepithelialtrans–differentiationduringdevelopment. Keywords: Carcinomas,Generegulatorynetworks,Epigeneticlandscape,Booleanmodels,Phenotypicattractors